Effect of furnace atmosphere on the calcination TG curves of natural limestones and dolomites - (:unkn) unknown (Elsevier BV, 1993)
1. Abstract Two different gaseous atmospheres were employed to examine the changes of calcination TG curves of 20 natural limestone and 6 dolomite samples from various parts of Turkiye. Calcination TG curves of these samples were obtained in atmospheres of 1) pure nitrogen; and 2) 15% by volume CO 2 in dry air, and they were recorded under non-isothermal conditions. It was found that, initial and final calcination temperatures were effected by furnace atmosphere. Also, the shape of TG curves of both limestone and dolomite samples were strongly effected from CO 2 partial pressure. All samples were sulfated in a tube furnace at a constant temperature of 1173 K. The composition of the gaseous mixture used in the sulfation experiments was 15 vol % CO 2 , 0.35 vol % SO 2 and balance of dry air by volume. Total sulfation capacities of the calcines prepared from limestone samples range from 0.381 to 0.686 (mg SO 3 /mg sorbent) and those from dolomite samples range between 0.321-0.498 (mg SO 3 /mg sorbent).